The INFLUENCE OF E-WALLET USAGE IN TRIGGERING IMPULSE BUYING (A Comparative Study Between Gen X And Gen Z Consumers In Bandung) - Reza Daradinanti; Diana Sari (Journal of Business Studies and Management Review, 2025)
This study investigates the influence of e-wallet usage in triggering impulse buying behavior in Generation X and Generation Z consumers in Bandung. Through a comparison of the two generational, the research aims to identify the key drivers that enhance impulsive purchasing tendencies facilitated by digital wallets. Data was collected through surveys, and statistical analysis was performed to validate the hypothesis that e-wallet features such as usability and compatibility significantly affect impulse buying. The findings highlight key differences between Gen X and Gen Z in their use of e-wallets and their resultant impact on consumer purchasing behaviors.